1,1?-(Propane-1,3-diyl)bis[2-(methylsulfanyl)-1H-benzimidazole] dihydrate - Yuksektepe, Cigdem; Caliskan, Nezihe; Genc, Murat; Servi, Suleyman; Buyukgungor, Orhan (Int Union Crystallography, 2007)
In the title compound, C19H20N4S2 center dot 2H(2)O, the two 1H-benzimidazole groups are bridged by a propane chain; the dihedral angle between the benzimidazole ring systems is 74.61 ( 3)degrees. The organic molecules and solvent water molecules form O - H center dot center dot center dot N hydrogen bonds. There are also O - H center dot center dot center dot O, C - H center dot center dot center dot S, C - H center dot center dot center dot pi and pi - pi interactions in the crystal structure.
Keywords: Benzimidazoles